Effectiveness of Journal Writing in Supporting Skills in Writing English Essay - Bambang Yudi Cahyono (Universitas Negeri Malang, 2016)
This research was aimed at knowing the effectiveness of providing journal writing in supporting the students' skills in writing English essay. The subjects were English department students who took Writing III course in the academic year of 1995/1996. This study involved two intact groups of students. The experimental group was given weekly journal writing, while the control group followed the regular writing. At the end of the treatment, writing tests on free topics were assigned and the students' works were scored using ESL Composition Profile. The result of analysis using t-test indicated that journal writing scores of the students from the two groups were not significantly different. However, students' responses indicated positive evaluation on the application of journal writing